Pola Gerak Tema pada Tulisan Mahasiswa Tingkat III Jurusan Bahasa dan Sastra Inggris UNP: Analisis tentang Kepaduan Teks - Rusdi Noor Rosa (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2011)
The aim of this research is to find out the types of thematic progression used by the third year students of English Department at State University of Padang. To achieve that purpose, content analysis is chosen as the design of the research method. The findings of this research show that the ability of the students in writing is still low. This is proved by the students’ weaknesses in using thematic progression in their writing. This problem leads to the students’ insufficient ability to provide logical arguments in their writing. Keywords: theme and rheme, thematic progression, writing, cohesion